2023
DOI: 10.3390/diagnostics13132282
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Segmentation and Classification of CT-Scanned Ovarian Tumours Using U-Net and Deep Convolutional Neural Networks

Ashwini Kodipalli,
Steven L. Fernandes,
Vaishnavi Gururaj
et al.

Abstract: Difficulty in detecting tumours in early stages is the major cause of mortalities in patients, despite the advancements in treatment and research regarding ovarian cancer. Deep learning algorithms were applied to serve the purpose as a diagnostic tool and applied to CT scan images of the ovarian region. The images went through a series of pre-processing techniques and, further, the tumour was segmented using the UNet model. The instances were then classified into two categories—benign and malignant tumours. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…[32,33]. The U-Net architecture derives its U-shape due to the sequentially arranged encoder and decoder modules [30,31,34]. The encoder consists of convolutional layers, batch normalization (BN) function, activation layers, and max pooling layers to realize the unique features in a given image.…”
Section: Proposed Structure Of the Volumetric Prediction Pipelinementioning
confidence: 99%
See 1 more Smart Citation
“…[32,33]. The U-Net architecture derives its U-shape due to the sequentially arranged encoder and decoder modules [30,31,34]. The encoder consists of convolutional layers, batch normalization (BN) function, activation layers, and max pooling layers to realize the unique features in a given image.…”
Section: Proposed Structure Of the Volumetric Prediction Pipelinementioning
confidence: 99%
“…U-Net-based architectures are one of the widely used structures in the field of medical image segmentation, such as breast tumor image segmentation, as it can work with small training data yet produce accurate results of image segmentation [32,33]. The U-Net architecture derives its U-shape due to the sequentially arranged encoder and decoder modules [30,31,34]. The encoder consists of convolutional layers, batch normalization (BN) function, activation layers, and max pooling layers to realize the unique features in a given image.…”
mentioning
confidence: 99%
“…The author obtained an accuracy of 90.2% using these ML models. Kodipalli & Devi, 2023;Kodipalli, Devi, et al, 2022;Kodipalli, Guha, et al, 2022;Kodipalli, Gururaj, et al, 2023;Ruchitha et al, 2022), contributed extensively to the detection of PCOS using a questionnaire and found that Fuzzy TOPSIS outperformed the SVM algorithm (Kodipalli & Devi, 2021). Watershed and active contour random walker were used in (Ruchitha et al, 2022) for segmenting the ovarian tumour and it was found that the watershed algorithm outperformed the active contour random walker algorithm.…”
Section: Ovarian Cancer Using Machine Learning Algorithmsmentioning
confidence: 99%
“…The novel inverted fuzzy c means architecture for the accurate detection of ovarian tumours was proposed in (Kodipalli, Fernandes, et al, 2023). The performance of UNet and Transformers was compared in (Kodipalli, Gururaj, et al, 2023) and it was observed that Transformers performed better in malignant lesion detection.…”
Section: Literature Surveymentioning
confidence: 99%